Biogenic Synthesis of Antibacterial, Hemocompatible, and Antiplatelets Lysozyme Functionalized Silver Nanoparticles through the One-Step Process for Therapeutic Applications - Pravin Dudhagara (Processes, 2022)
To evaluate silver nanoparticles’ (AgNPs) therapeutic and clinical potentials, antibacterial action, blood compatibility, and antiplatelet activities are the main concerns for toxicity profiling. Heat-denatured lysozyme-mediated formulation stabilized the AgNPs, thereby providing more bactericidal activity and blood compatibility. The study of the synthesis of AgNPs suggests the rapid and cost-effective formulation of AgNPs by one-step reaction using a 10:1 ratio of silver nitrate and lysozyme by incubating at 60 °C for two hours. Characterization of AgNPs was analyzed by UV–Visible spectroscopy, DLS, TEM, EDX, XRD, AFM, and FTIR, followed by antibacterial, hemocompatibility, and platelet aggregation testing. The average size of synthesized AgNPs was found to be 94.10 nm with 0.45 mV zeta potential and 0.293 polydispersity index by DLS. The TEM and EXD results indicated homogeneously 28.08 nm spherical-shaped pure formations of AgNPs. The XRD peaks showed the synthesis of small AgNPs with a crystallite size of 22.88 nm, while the AFM confirmed the homogeneity and smoothness of the monodispersed AgNPs. The FTIR spectra specified the coating of the lysozyme-derived amide group on the AgNPs surface, which provides stability and functionality of nanoparticles. The antibacterial activity of AgNPs was remarkable against six pathogenic bacteria and three multidrug resistance (MDR) strains (i.e., Escherichia coli, Klebsiella aerogenes, and Pseudomonas aeruginosa), which exhibited inhibition zones with diameters ranging between 13.5 ±  0.2 mm to 19.0 ±  0.3 mm. The non-hemolytic nature of the AgNPs was calculated by percentage hemolysis with four concentrations. The negative result of platelet aggregation using platelet-rich plasma suggests the antiplatelet effect of AgNPs. Only minor hemolysis of 6.17% in human erythrocytes and mild platelet aggregation of 1.98% were induced, respectively, by the use of 1000 µL of 1 mM AgNPs, which contains approximately 107.8 μg silver. The results indicated that the antiplatelet potency and non-hemolytic nature with the antibacterial action of the lysozyme functionalized AgNPs have a good chance to be used to solve in-stent restenosis and thrombosis issues of the coronary stent and may also have a possibility to use in vaccination to resolve the blood clotting problem. So, the optimized biogenic formulation of AgNPs offers promising opportunities to be used as a therapeutic agent.